The Influence of Pedagogical and Personality Competence on the Professional Competence of Elementary School Teachers with the Moderation of Organizational Culture - Asmawi Asmawi; Renita Renita; Iis Sutiawati; Hamidah Hamidah; Mutoharoh Mutoharoh (Universitas Muhammadiyah Mataram, 2026)
Ensuring primary school teachers possess adequate competency standards is a fundamental necessity for achieving quality educational outcomes, yet sharp gaps in professional execution persist in the field. Professional competence does not stand alone but is rather the result of the accumulation of various other dimensions of ability, including pedagogical competence and personality competence. The primary objective of this study is to empirically analyze the influence of pedagogical competence and personality competence on teacher professional competence, as well as to examine the role of organizational culture as a moderating variable in this relationship. This quantitative research with a causal associative design was conducted systematically in Serang City during the first and second weeks of May 2026. The target population comprised elementary school teachers, from which a sample of 117 respondents was selected using a combination of convenience and quota sampling techniques. Criteria for selection required a minimum Bachelor's degree (S1) and two years of institutional tenure. Data collection was carried out using anonymous, structures online questionnaires based on a five-point Likert scale, which were pre-tested and declared highly reliable (Cronbach's Alpha > 0.80). The compiled data were analyzed using descriptive statistics and inferential analysis through hierarchical Moderated Regression Analysis (MRA). ThThe results show that pedagogical competence and personality competence are crucial determinants that exert a positive and significant direct influence on improving the professional competence of elementary school teachers. Statistical estimation demonstrates that pedagogical competence holds the most dominant direct impact (β = 0.475, p < 0.001), followed by personality competence (β = 0.292, p = 0.001), and a direct contribution from organizational culture (β = 0.214, p = 0.004). The overall model exhibits high predictive validity and statistical fit (R2 = 0.570, F-test p < 0.001), explaining 57.0% of the variance in professional competence. On the other hand, organizational culture has not been proven to significantly moderate the relationship between individual competence and professional competence, indicated by non-significant interaction coefficients for both pedagogical (β = 0.039, p = 0.592) and personality paths (β = 0.049, p = 0.478). The model's explanatory change was minor (ΔR2 = 0.006), confirming that adding the interaction fields adds a negligible 0.6% to the model. This implies that teacher professionalism operates with high intrinsic autonomy and is driven more by individual capacity rather than environmental or organizational fluctuations.